Assessing executive functions in free-roaming 2- to 3-year-olds - Schröer, Lisanne; Cooper, Richard P.; Mareschal, Denis (Frontiers in Psychology, 2023)
Core aspects of executive functions (EFs) are known to be related to academic skills such as literacy and numeracy. However, school outcomes may also be related to higher-level executive functions such as planning. Yet little work has looked at assessing natural manifestations of higher-level EFs in children who are on the cusp of entering formal schooling. One reason for this is the difficulty of obtaining ecologically valid measures of EFs that are suitable for use in children from 2 years of age. In the current study, we suggest that a naturally occurring play behaviour can be used to assess higher-level EFs in nursery-aged children. We describe a novel task – building a striped Duplo tower subject to two constraints – designed to assess planning in a real-world multi-action situation. Performance on this task was found to vary with age. Importantly, distinct components of multiple constraint planning performance predicted laboratory-based measures of inhibitory control and working memory efficacy. Thus, this task provides a simple, cheap and effective way of assessing executive function in very young children through the observation of natural behaviours. It also opens up possibilities to investigate the neurodevelopment of EF in the real-world.